Chemistry and Structures of Hexakis(halogenomethyl)‐, Hexakis(azidomethyl)‐, and Hexakis(nitratomethyl)disiloxanes. Issue 28 (31st May 2013) - Ascherl, Laura; Evangelisti, Camilla; Klapötke, Thomas M.; Krumm, Burkhard; Nafe, Julia; Nieder, Anian; Rest, Sebastian; Schütz, Christian; Suceska, Muhamed; Trunk, Matthias
Abstract: An investigation of the structures and chemistry of substituted hexamethyl disiloxanes ((XCH2 )3 Si)2 O; X=F, Cl, Br, I, N3, and ONO2 ) is reported. New synthetic routes to the precursor hexakis(chloromethyl)disiloxane are presented. The products with X=Cl, Br, I, and N3 were characterized by NMR, IR, and Raman spectroscopy. In addition, the single‐crystal structures of the products with X=Cl, Br, and I are discussed in detail. The compounds with X=F and ONO2 were not obtained in their pure form; instead investigations of the decomposition products revealed their conversion into intermediates. Theoretical calculations of the gas‐phase structures at the B3LYP/cc‐pVDZ, B3LYP/3‐21G, MP2/6‐31G*, and MP2/3‐21G levels of theory are used to explain the chemical and physical behavior of the compounds with X=Cl, Br, I, N3, and ONO2 . A new decomposition pathway of hexakis(nitratomethyl)disiloxane is presented and is used to explain their remarkable instability. The energetic properties and values of the nitrate and azide derivatives were calculated at the CBS‐4M level of theory by using the improved EXPLO5 computer code version 6.01. Abstract : Halogen substitution in disiloxanes : Hexakis(halogenomethyl)disiloxanes (X=Cl, Br, I) are precursors of energetic hexakis(azidomethyl)‐ and hexakis(nitratomethyl)disiloxanes (see figure). Their remarkable sensitivity is discussed and a decomposition pathway is proposed.